Alcohol and Drug Screening, Brief Intervention, and Referral to Treatment (SBIRT) Training and Implementation: Perspectives from 4 Health Professions. Issue 4 (July 2018) - Wamsley, Maria; Satterfield, Jason M.; Curtis, Alexa; Lundgren, Lena; Satre, Derek D.
Abstract : Objectives: Screening, Brief Intervention, and Referral to Treatment (SBIRT) can effectively identify and address substance misuse and substance use disorders (SUDs), and can be delivered by a range of trained health professionals. Yet, barriers remain to effective training and implementation of SBIRT in health and social service settings, and models of interprofessional collaboration in SBIRT delivery are underdeveloped. Methods: We reviewed current literature regarding SBIRT effectiveness, training, and implementation by physicians, nurses, psychologists, and social workers. An SBIRT expert and representative from each health profession synthesized literature and training experiences to inform the development of interprofessional training and collaborative implementation strategies. Results: Each of the health professions involved in SBIRT training and implementation have strengths and weaknesses that influence how SBIRT is taught, learned, and delivered. Some of these are specific to the components of SBIRT, for example, screening versus brief intervention, whereas others depend on profession-driven competencies, for example, motivational interviewing. Professional organizations have encouraged a range of tailored SBIRT training initiatives, but true interprofessional training and the implementation of collaborative, team-based care are largely unrealized. Conclusions: SBIRT can be a valuable approach to screening and treatment for SUDs when delivered by a range of healthcare professionals. A more nuanced understanding of the assumptions and characteristics of each profession, informed by the emerging field of implementation science, may shape more effective training curricula and highlight interprofessional models of SBIRT delivery that maximize the strengths of each profession.